1997
DOI: 10.1117/12.274700
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-tail-buffeting alleviation using piezoelectric actuators: some results of the actively controlled response of buffet-affected tails (ACROBAT) program

Abstract: A 1/6-scale F-18 wind-tunnel model was tested in the Transonic Dynamics Tunnel at the NASALangley Research Center as part of the Actively Controlled Response Of Buffet Affected Tails (ACROBAT) program to assess the use of active controls in reducing vertical tail buffeting. The starboard vertical tail was equipped with an active rudder and the port vertical tail was equipped with piezoelectric actuators. The tunnel conditions were atmospheric air at a dynamic pressure of 14 psf. By using single-input-single-ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 12 publications
0
16
0
3
Order By: Relevance
“…The study is motivated by the application of piezoelectric actuators for alleviating the "tail buffeting" problem in a twin tail aircraft [10]. The buffet loads acting on the tail surface cause excessive wear and tear that significantly reduce the lifetime of the aircraft and increase repair and maintenance costs.…”
Section: Analysis and Optimization Of Smart Actuatorsmentioning
confidence: 99%
“…The study is motivated by the application of piezoelectric actuators for alleviating the "tail buffeting" problem in a twin tail aircraft [10]. The buffet loads acting on the tail surface cause excessive wear and tear that significantly reduce the lifetime of the aircraft and increase repair and maintenance costs.…”
Section: Analysis and Optimization Of Smart Actuatorsmentioning
confidence: 99%
“…Their analysis indicated that more than a 50 percent reduction in the root mean square (rms) strain at the root of the tail could be achieved at selected flight conditions with a smart material system. Moses 18,19 and Hauch et al 20 separately investigated active buffeting alleviation control systems utilizing piezoelectric strain actuators (among other strategies) on sub-scale, twin-tail, fighter-like aircraft models. Both researchers found that active control systems can significantly reduce buffeting.…”
Section: Past Alleviation Techniquesmentioning
confidence: 99%
“…Of Buffet-Affected Tails) program at the LaRC, feedback control to the rudder on the starboard fin and to piezoelectric patches on the port fin were implemented to reduce fin buffeting on a 1/6-scale fullspan F/A-18 model 18,19 . The rms value of the root bending moment was reduced by as much as 20% using magnitudes well below the physical limits of the actuators.…”
Section: During the Acrobat (Actively Controlled Responsementioning
confidence: 99%
“…Um outro grande programa envolve pesquisas para controle ativo de buffeting utilizando materiais piezelétricos nas empenagens verticais da aeronave F/A-18 (MOSES, 1997(MOSES, , 1999DÜRR, 1998;HOPKINS et al, 1998). Estes estudos apresentam testes em túnel de vento com um modelo de aeronave em escala dinâmica (MOSES, 1997), até ensaios em solo com uma aeronave real (MCGOWAN et al, 1998;HOPKINS et al 1998;MOSES, 1999).…”
Section: Controle Ativo Utilizando Materiais Piezelétricosunclassified
“…Por exemplo, o controle ativo de flutter utilizando atuadores piezelétricos apresentado por Heeg (1993), o programa da NASA "Piezoelectric Aeroelastic Response Tailoring Investigation (PARTI)" desenvolvido para controle de flutter e atenuação da resposta a rajada (MCGOWAN et al, 1998) e os trabalhos apresentados para controle ativo de buffeting utilizando materiais piezelétricos nas empenagens verticais da aeronave F/A-18 (MOSES, 1997(MOSES, , 1999DÜRR, 1998;HOPKINS et al, 1998). Uma revisão bastante abrangente sobre o uso de materiais inteligentes em soluções de problemas aeroelásticos é apresentada por Giurgiutiu (2000).…”
Section: Introdução Introduçãounclassified